2021
DOI: 10.1007/s11356-021-12446-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impacts of microbial plant protection products containing Bacillus thuringiensis on the survival of adults and larvae of the honeybee (Apis mellifera)

Abstract: This study was aimed at evaluating the effect of a microbial pest-controlling product (MPCP) with the active substance Bacillus thuringiensis ssp. aizawai (strain: ABTS-1857) on adults and larvae of honeybees. To determine the contamination levels of Bt spores in different matrices, a colony-feeding study under semi-field conditions was performed. Furthermore, two chronic adult trials and a chronic larval study were conducted under laboratory conditions to test the effects of different concentrations of the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Some reviews summarize the potential of isolated Xn or Bt in the biological control of vectors and insect species harmful to agriculture [ 18 , 44 , 45 , 46 , 47 ]. However, the efficacy of these pathogens, when used in single, does not always provide satisfactory results; in addition, their efficacy often requires high concentrations of the pathogen, which can interfere with the life cycle and affect other beneficial organisms present in the environment [ 48 , 49 ]. The reduction of the administered concentrations and the improvement of the rapidity of action, could be achieved by combining different bioinsecticides, thus by exploiting the possible synergistic or additive potential of the applied pathogens [ 9 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some reviews summarize the potential of isolated Xn or Bt in the biological control of vectors and insect species harmful to agriculture [ 18 , 44 , 45 , 46 , 47 ]. However, the efficacy of these pathogens, when used in single, does not always provide satisfactory results; in addition, their efficacy often requires high concentrations of the pathogen, which can interfere with the life cycle and affect other beneficial organisms present in the environment [ 48 , 49 ]. The reduction of the administered concentrations and the improvement of the rapidity of action, could be achieved by combining different bioinsecticides, thus by exploiting the possible synergistic or additive potential of the applied pathogens [ 9 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colonies were identified as Bt by qPCR, amplifying a partial sequence of the CryIAa gene (Ogunjimi et al 2000;Steinigeweg et al 2021). Accordingly, a random colony was resuspended in 50-µL ddH 2 O, followed by bacterial lysis at 95 °C for 15 min.…”
Section: Identification Of Potential Bt Coloniesmentioning
confidence: 99%
“…Several reports regarding direct and indirect cross-effects of Bt formulations and their toxins across insect taxa and orders recently indicated the semi-specificity of Bt (van Frankenhuyzen 2017; Redmond et al 2020;Coyle et al 2000;Babin et al 2020;Nawrot-Esposito et al 2020;Tudoran et al 2020). Lepidopterantargeted formulation, containing Bta ABTS 1857, has demonstrated increasing mortality of adult and larvae of honeybees after chronic exposure under laboratory conditions (Steinigeweg et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that, after being treated with Bt for 24 h, V. destructor trembled, regurgitated, with intestinal inflammation (dysentery) and eventually died [ 211 , 212 , 213 ]. Short-term experiment showed no lethal effects among A. mellifera adults or larvae and possibly reduced vertical displacement [ 213 , 214 ] whereas chronic exposure to Bt induced precocious mortality for adults and larvae bees [ 215 ]. A lack of field studies does not allow to consider Bt as a resolutive method against the mite.…”
Section: Biocontrol and Ipm Strategies For V Destructor Managementmentioning
confidence: 99%